Kompleksitas Argumentasi Berbasis Isu Sosiosaintifik pada Jenjang SD, SMP, dan SMA - Amalia, Nur Fildzah; Riandi, Riandi; Widodo, Ari; Rochintaniawati, Diana (Department of Biology Education, Universitas Pendidikan Indonesia, 2018)
The Student’s argument can be raised and developed using socioscientific issues. Socio-scientific issues about health is one of the social problems that the subject of public debate. This study aims to describe the complexity of the arguments in elementary school, middle school, and high school. The three level of education is a school which is shaded by one of the Foundation in Bandung. Participants involved in the study consisted of 31 elementary students, 14 middle school students, and 23 high school students. Data taken using a quisioner consist of five items concerning socioscientific issues as well as individual interviews based on the answers to the test written description. Data identified using Toulmin Argumentation Adaptation Pattern (TAP), which consists of four levels, namely, level 1 (claim), level 2 (claims, data and / or warrants), level 3 (claims, data / warrant, backing), and level 4 (claims, data / warrant, backing, qualifier). The results showed that the development of increasingly rising complexity of arguments according to their level. The complexity of the arguments on elementary students reached level 2-3, middle school and high school reached level 3. Percentage of level 3 more ascending towards the middle school to high school. Meanwhile, if viewed from the dominates of the arguments category level, level 2 emerged as the dominant category in elementary school, middle school, and high school.